Ophthalmologists’ awareness of cerebral visual impairment – preliminary study - Stanimirov, Ksenija; Grbović, Aleksandra; Anđelković, Marija; Ljutica, Milorad; Rakić, Sanja (Specijalna edukacija i rehabilitacija, 2021)
Introduction. Cerebral visual impairment is the leading cause of severe visual impairment and blindness in infants and children in high-income countries. The main cause of this condition is damage of higher visual pathways and brain centers which leads to problems in processing visual information. In the last 20 years, an increase in the prevalence of cerebral visual impairment has been observed, but this diagnosis as a cause of vision problems in Serbia is not common. Objectives. The aim of this study was to assess the awareness of ophthalmologists of cerebral visual impairment. Methods. The Questionnaire for the assessment of cerebral visual impairment (Maitreya et al., 2018) was translated into Serbian, and used for data collection. The sample consisted of 45 ophthalmologists employed on the territory of the Republic of Serbia. Results. Two thirds of ophthalmologists from the sample self-assessed their knowledge as low (or nonexistent). However, the results showed that they had a satisfying level of awareness about cerebral visual impairment, and the majority of the participants correctly stated the most common risk factor for cerebral visual impairment. The highest awareness was observed in ophthalmologists who worked in health centers, those with more work experience, and especially those who primarily worked with children. Conclusion. Further informing the ophthalmologists about the diagnostic method of choice, symptomatology and differential diagnosis of cerebral visual impairment is desirable. Raising the awareness of doctors about this condition would lead to more frequent diagnoses, especially in babies with neurological impairments that are currently most likely misdiagnosed or unrecognized when it comes to their vision problems.